Exploring the Potential of 3D Printing Production Model to Promote Sustainable Development - Chatzi-Rodopoulou, Dora; Fronimaki, Evgenia; KadrefI, Athanasia; Koltsaki, Maria (Journal of Engineering and Applied Sciences Technology, 2025)
Nowadays, in this volatile post-Covid era, there is an urgent need to develop new and more sustainable production models. The role of industrial production is crucial as it influences the EU economic resilience, it has a significant footprint on the environment while greatly affecting the social well-being of EU citizens. 3D printing is an expanding additive manufacturing technology with many applications in various industrial sectors. It involves the layer-by-layer fabrication of products through a CAD model or a 3D scanner output. The integration of 3D printing into the production process is increasingly attracting the interest of stakeholders. 3D printing technology provides access and participation in the production process to both producers and end-consumers. Despite the multitude of challenges, 3D printing is gaining ground, paving the way for innovative production while promising to promote a new model of sustainable industrialization